A case of anti-MDA5 antibody-positive dermatomyositis developing reversible cerebral vasospasm syndrome successfully treated by multi-immunosuppressant combination including mycophenolate mofetil. (2nd January 2021) - Muramatsu, Takumi; Tono, Toshihiro; Kanayama, Yoshiro; Hasegawa, Yasuhiro; Kondo, Junichi; Hoshiyama, Takayuki; Wada, Tatsuhiko; Arinuma, Yoshiyuki; Tanaka, Sumiaki; Yamaoka, Kunihiro
Abstract: A 39-year-old woman admitted with multiple joint pain, hand rashes, and shortness of breath was diagnosed with anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive dermatomyositis (DM) with interstitial pneumonia (IP). Because of progressive dyspnoea and hypoxaemia, her IP was considered rapidly progressive interstitial lung disease. Initially, prednisolone 60 mg/day, cyclosporine A (CyA), and intravenous cyclophosphamide (IVCY) were initiated. A few days following the initiation of treatment, she experienced massive thunderclap headache, which was diagnosed as reversible cerebral vasospasm syndrome based on the findings of contraction in cerebral arteries with brain magnetic resonance imaging. Treatment with CyA and IVCY was discontinued, and diltiazem and mycophenolate mofetil (MMF) were initiated as an alternative immunosuppressant. Considering IVCY as the cause of Reversible cerebral vasospasm syndrome based on her clinical course, tacrolimus was commenced, which improved both DM and IP. DM patients who are anti-MDA5 antibody-positive are considered to have poor prognosis and require aggressive immunosuppressive treatments. In patients experiencing adverse events with standard IVCY, MMF with high-dose steroids and alternative calcineurin inhibitor should be considered.